2013
DOI: 10.1111/rda.12261
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Maturation of Oocytes from Santa Ines Ewes Subjected to Consecutive Sessions of Follicular Aspiration by Laparoscopy

Abstract: The success of embryo production in vitro depends upon the use of an efficient oocyte retrieval technique, and the best results have been obtained by laparoscopic aspiration. The aim of this study was to evaluate the effect of consecutive sessions of follicular aspiration on the quantity, quality and in vitro maturation competence of oocytes obtained from ewes subjected to hormonal stimulation. Six Santa Ines ewes underwent nine sessions of follicular aspiration by laparoscopy with a 7-day interval between ses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 37 publications
2
3
0
Order By: Relevance
“…D‐cloprostenol dose used in those females was also adopted based on work with small ruminants and small rodentia. However, in all those studies, the doses shown to be efficient, since it was not reported significant presence of corpus luteum in all of them, corroborating our responses (Padilha et al, ). In small rodentia, cloprostenol administered in higher dosis is efficient mainly if combined with progesterone, reaching up to 100% the response in oestrous synchronization and ovulation (Pallares & Gonzalez‐Bulnes, ).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…D‐cloprostenol dose used in those females was also adopted based on work with small ruminants and small rodentia. However, in all those studies, the doses shown to be efficient, since it was not reported significant presence of corpus luteum in all of them, corroborating our responses (Padilha et al, ). In small rodentia, cloprostenol administered in higher dosis is efficient mainly if combined with progesterone, reaching up to 100% the response in oestrous synchronization and ovulation (Pallares & Gonzalez‐Bulnes, ).…”
Section: Discussionsupporting
confidence: 89%
“…Recovery and maturation rates did not differ during the periods of the experiment. Similar results were found in sheep (Padilha et al, ; Teixeira et al, ), but it was observed a decrease in oocyte quality in goats (Cordeiro et al, ) and cows (Broadbent, Dolman, Watt, Smith, & Franklin, ) with repeated follicular aspirations. These results may suggest that spotted paca do not develop antibodies to FSH and eCG from the repeated use of these hormones.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Thus, the dynamic of cortical granules (CG) changes during oocyte development, and the CG staining pattern has been used in different species as an indicator of cytoplasmic maturation (Carneiro et al 2002;Takano et al 2002;Liu et al 2005;Padilha et al 2014). In the dog, there is only one report that investigates the relationship between cortical granule distribution and chromatin configuration during in vitro maturation through CG staining using Hoescht-fluorescein isothiocyanate-conjugated Lens culinaris agglutinin (FITC-LCA; Apparicio et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Laparoscopic ovum pick-up (LapOPU) used for in vitro production (IVP) is one of the leading reproductive biotechniques in assisted reproduction, highlighted for being less invasive, provide a quicker recovery and the possibility of being held several times in the same female as already described in some domestic species (Teixeira et al, 2011;Cordeiro et al, 2014;Padilha et al, 2014;Teixeira et al, 2015).…”
Section: Introductionmentioning
confidence: 99%